192 Study of endothelial function and vascular stiffness in patients affected by dilated cardiomyopathy on treatment with sacubitril/valsartan. (8th December 2021) - Amore, Ludovica; Alghisi, Fabio; Cersosimo, Angelica; Cimino, Giuliana; Pascariello, Greta; Pancaldi, Edoardo; Bernardi, Nicola; Calvi, Emiliano; Lombardi, Carlo; Vizzardi, Enrico; Metra, Marco
Abstract: Aims: It has already been demonstrated the efficacy of sacubitril/valsartan in the treatment of heart failure with reduced ejection fraction, but many of its properties are still unknown especially regarding its effects on endothelial dysfunction and arterial stiffness. Methods and results: To this purpose, a longitudinal study involving 15 patients with dilated cardiomyopathy with reduced left ventricular ejection fraction (LVEF) was started; the purpose was collecting at the beginning and at the end of the study blood pressure measurements, transthoracic echocardiography images, parameters of endothelial function with peripheral arterial tonometry (EndoPAT ® ), and non-invasive evaluation of the aortic stiffness parameters by using applanation tonometry (SphygmoCor ® Px system). Aortic stiffness parameters weren't different at 6 months, compared to baseline. There was a slight, not significant increase in augmentation pressure ( P = 0.889), augmentation index ( P = 0.906), and sphygmic wave velocity ( P = 0.263). Systolic, diastolic, and differential central arterial pressure didn't change. RHI (reactive hyperaemia index) increased significantly after 6 months ( P = 0.001) as well as augmentation index corrected for 75 b.p.m. Ejection fraction (32.21% ± 5.7 to 38.43% ± 8.4; P = 0.010) and diastolic dysfunction degree ( P = 0.021) improved significantly. Mitral regurgitation improvement wasn't statistically significant ( P = 0.116). Tricuspid annular plane systolic excursion didn't change while pulmonary systolic arterial pressure increased, although not significantly (22.83 mmHg ± 4 to 27.33 mmHg ± 6; P = 0.068) and within the normal range values. Conclusions: Sacubitril/valsartan can improve endothelial function significantly in patients with dilated cardiomyopathy and reduced LVEF. It can also improve left ventricular function, mitral regurgitation, and diastolic function. Conversely, this drug seems to have no effects on vascular stiffness.